Kajian Pengembangan Kewirausahaan pada Kawasan Transmigrasi - Novita Wahyu Setyawati (Jurnal Maksipreneur, 2019)
The development of entrepreneurship in transmigration areas is obstacles so that targets cannot be achieved effectively. This study aims to: (1) study the development of entrepreneurship implemented in the transmigration community; (2) reviewing the obstacles to developing entrepreneurship in transmigration areas; and (3) formulating efforts needed to increase entrepreneurship development in trans-migration areas. The study was conducted with a qualitative approach with the type of descriptive research in the Musi Rawas area. The results of the study indicate that the development of entrepreneurship has increased capabilities and is beneficial for business development, but has not effectively increased entrepreneurship and business development capabilities. In general, the constraints of developing entrepreneurship are not focused, diffusion of knowledge, and skills are not effective, have not been connected with entrepreneurship development programs in other technical sectors/ units, and there has been no change in the way of thinking in formulating business development needs.